Forming a solidarity discourse through transtextual practice: Case study of Yamada Bimyō’s works on the Philippines - Sztafiej, Przemysław (Silva Iaponicarum, 2025)
Networking should be considered an important aspect of the history of pan-Asian thought. The Philippine Revolution (1896–98) and the Philippine-American War (1899–1902) provide an example of events that helped form unexpected links. Mariano Ponce’s stay in Japan to lobby for support of the revolution influenced Yamada Bimyō to publish a series of works in 1902–1903. This article provides an analysis of Yamada’s techniques for creating a discourse of Japanese-Filipino solidarity in Momoiroginu and Aginarudo: Firipin Dokuritsu Senwa. While Yamada is frequently mentioned in studies of the Japanese reception of the Philippine Revolution, there is no in-depth analysis of these texts. To fill this gap, I employ Gérard Genette’s concept of transtextuality to first, show how Yamada referenced/rewrote his sources while simultaneously inserting original ideas and second, to address the fact that one of Yamada’s texts was transtextually re-contextualized during the Pacific War.